2021
DOI: 10.1111/tbed.14310
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Senecavirus A in animal feed ingredients and infection following consumption of contaminated feed

Abstract: Animal feed and feed ingredients have recently been investigated as sources of pathogen introduction to farms and as a potential source of infection to animals postconsumption of contaminated feed. Survival of several viruses for a prolonged period has been demonstrated in feed. Here, we determined the rate of decay of Senecavirus A (SVA) in swine feed ingredients as a function of time and temperature and established half-life estimates for the virus. Select feed ingredients were spiked with a constant amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 31 publications
(47 reference statements)
1
24
0
Order By: Relevance
“…Therefore, it is plausible that flies may be infected with comparable viral titers during feeding in naturally infected pig secretion, feces, or tissues. Whereas the SVA minimal infectious dose is unknown, a previous study demonstrated that pigs fed for three consecutive days with feed spiked with SVA containing doses as low as 10 5.0 TCID 50 /mL had RNA present in the feces and tonsils, and most of the exposed pigs also had viremia [12]. The prolonged viability of SVA in house flies may provide an opportunity for pathogen transfer over some distances due to the house fly flight range.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is plausible that flies may be infected with comparable viral titers during feeding in naturally infected pig secretion, feces, or tissues. Whereas the SVA minimal infectious dose is unknown, a previous study demonstrated that pigs fed for three consecutive days with feed spiked with SVA containing doses as low as 10 5.0 TCID 50 /mL had RNA present in the feces and tonsils, and most of the exposed pigs also had viremia [12]. The prolonged viability of SVA in house flies may provide an opportunity for pathogen transfer over some distances due to the house fly flight range.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in the viability of both SVA and SwPV in exposed flies are remarkable. Both viruses are known to be highly resistant under environmental conditions [12,25,26]. Whereas the study was not designed to identify whether the infectious virus was retrieved from the internal or external parts of the flies, one hypothesis for the prolonged SVA viability compared to SwPV is that SVA resisted the enzymatic digestion process in the flies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Senecavirus A continues to be an issue for swine producers as vectors, including mice and flies, are involved in the transmission of the virus within and between farms 4 , and SVA has been shown to be stable in several swine feed ingredients for up to a month 28 . Although vaccines are being developed, they have not conferred prolonged protection 29 ; thus, warranting the need for new strategies, such as gene editing that have resulted in resistance to porcine reproductive and respiratory syndrome virus (PRRSV) and transmissible gastroenteritis virus (TGEV) 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Following the case studies are original articles, which bring forth new information regarding the stability and infectivity of foot and mouth disease virus (Stenfeldt et al, 2021), and Seneca Virus A (Caserta et al, 2021) in feed, the oral infective dose in feed, and the efficacy of feed additives as mitigants to reduce risk. We then explore the ability to sample feed correctly to maximise the sensitivity and specificity of detection, as well as how to manage viral contamination of feed at the level of the farm and the feed mill.…”
mentioning
confidence: 99%